PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DAN MEDIA POP UP BOOK UNTUK MENINGKATKAN KETERAMPILAN BERCERITA SISWA KELAS IV SEKOLAH DASAR - Agni Kusuma Wardani; Lia Mareza; Dedy Irawan (Jurnal Riset Pendidikan Dasar (JRPD), 2020)
Abstract. This research is motivated by the low student storytelling skills. This study aims to describe storytelling skills using discovery learning and pop up book media models. This research technique uses classroom action research (CAR), which was carried out in two cycles and used the research design of Kemmis & McTaggart. Data collection techniques used are observation, tests, and documentation. The collected data was analyzed using qualitative and quantitative descriptive analysis techniques. The results of research conducted at Purbadana 2 Elementary School showed that learning using discovery learning assisted with pop up book media went well. The results of the knowledge skills in the first cycle reached an average of 3.1 with a percentage of completeness of 46%, meaning that students' storytelling skills were still included in the sufficient category. In the second cycle, the average was 3.9 with a percentage of completeness of 84%, meaning that students' storytelling skills were included in the criteria of good. Based on the results of the study, the application of the discovery learning learning model assisted by pop up book media can improve the skills of the fourth grade students in Purbadana 2 Elementary School.